COMPETENCY BASED TRAINING IN THE FACULTY ACCOUNTING STUDIES OF PUBLIC UNIVERSITIES IN PERU - Choy Zevallos, Elsa Esther (2010)
The problem in our country, many universities, both public and private, have yet to implement its skills-based curriculum Objective. Noted the importance of competency based training in public accounting career and establish the need to establish a standard model based on skills, in order that the curriculum of career public accountant increase their level of relevance, effectiveness and efficiency, and form competent professionals currently requires the job market. Material and methods. Presents a descriptive and analytical study, using information and legal instruments related to curriculum and competencies. Results. A model syllabus for competence to assess the competency standard. Conclusions. Some universities are currently developing curriculum for goals and have not seen a learning teaching skills training.